2020
DOI: 10.21511/im.16(4).2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Perceived usefulness of social media in financial decision-making: differences and similarities

Abstract: Financial decision-making through social media blogs and opinions is an area not much explored by the researchers. This study intends to understand the perceived usefulness of social media in financial decision-making amongst individuals and groups based on demographic similarities and social parameters. This paper aims to understand the perception of various subgroups in society within the large population sample. The paper applies Mann-Whitney and Kruskal-Wallis non-parametric tests to examine the proposed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(16 reference statements)
0
4
0
1
Order By: Relevance
“…В епоху інформаційного прогресу і діджиталізації, переходу маркетингових технологій в електронні ресурси та соціальні мережі виникають нові проблеми, пов'язані з впливом розповсюджених блогів і соціальних мереж на прийняття молоддю фінансових рішень. Науковці аналізують можливості й користь соціальних мереж в прийнятті фінансових рішень серед різних однорідних груп на основі демографічних даних в розвинутих європейських країнах (Khan, Akhtar & Tripathi, 2020). За результатами технічного й інформаційного прогресу помітний розширений перехід валютної системи в інформаційну, що сприяє широкому розповсюдженню електронних грошей і платіжних кредитних карт, які найбільш активно застосовує молодь.…”
Section: вступunclassified
“…В епоху інформаційного прогресу і діджиталізації, переходу маркетингових технологій в електронні ресурси та соціальні мережі виникають нові проблеми, пов'язані з впливом розповсюджених блогів і соціальних мереж на прийняття молоддю фінансових рішень. Науковці аналізують можливості й користь соціальних мереж в прийнятті фінансових рішень серед різних однорідних груп на основі демографічних даних в розвинутих європейських країнах (Khan, Akhtar & Tripathi, 2020). За результатами технічного й інформаційного прогресу помітний розширений перехід валютної системи в інформаційну, що сприяє широкому розповсюдженню електронних грошей і платіжних кредитних карт, які найбільш активно застосовує молодь.…”
Section: вступunclassified
“…In Japan, Fujiki (2020) explored the factors influencing the actual and intended sources of financial knowledge, finding that households choosing financial institutions and advisors had mainly older household heads and had more financial assets, a higher level of educational attainment, and a higher ratio of risky asset holdings for stocks and bonds. Khan et al (2020) analyzed the relationship between demographic and social parameters and the use of social media in financial decision making and found that cohort generation and occupation were significantly and favorably associated with the use of social media. Similarly, Cwynar et al (2019) examined the factors influencing the use of social media as an information source in finance in Poland and found that people with more diversified asset portfolios and those who hold the riskiest assets are more likely to use social media for information purposes.…”
Section: Introductionmentioning
confidence: 99%
“…First, sample selection and omitted variable bias are concerns. For example, Khan et al (2020) and Cwynar et al (2019) focused mainly on a specific area or small institutions, with limited use of important explanatory variables, thus questioning the representativeness and precision of the sample. Second, several studies suffer from a limited sample size bias.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations